2012
DOI: 10.1007/s13391-011-0510-3
|View full text |Cite
|
Sign up to set email alerts
|

Effects of process parameters in synthesizing Sn nanoparticles via chemical reduction

Abstract: In order to prepare solder particles for fine pitch interconnections, Sn nanoparticles were synthesized via chemical reduction methods. A number of the process parameters, i.e., injection rate of a precursor solution, application of sonication, reaction temperature, types of reaction medium and capping agent, and drying temperature, are varied in order to study their effect on this process. Using a methanol solution containing 1,10-phenathroline monohydrate, the size of Sn nanoparticles collected after the syn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
5
0

Year Published

2013
2013
2021
2021

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 16 publications
(6 citation statements)
references
References 15 publications
1
5
0
Order By: Relevance
“…Hence, it was confirmed that the synthesized nanoparticles agglomerated during the drying process, resulting in the formation of larger particles. This agglomeration, during drying, of nanoparticles capped with polyvinylpyrrolidone (PVP) has been reported previously as well [20]. The agglomerated particles were found to be not porous, but dense, as can be seen from Fig.…”
Section: Resultssupporting
confidence: 83%
“…Hence, it was confirmed that the synthesized nanoparticles agglomerated during the drying process, resulting in the formation of larger particles. This agglomeration, during drying, of nanoparticles capped with polyvinylpyrrolidone (PVP) has been reported previously as well [20]. The agglomerated particles were found to be not porous, but dense, as can be seen from Fig.…”
Section: Resultssupporting
confidence: 83%
“…The unwanted/undesired agglomeration is typically reduced by the surfactant. We used PVP as the most effective stabilizing agent avoiding nanoparticle agglomeration and surface oxidation [20–21] . The advantage of PVP as a stabilizing agent is the low influence of the particle growth, wide applications for nanoparticles stabilization and a high affinity to SnO x , the disadvantage is a higher crystallite size of prepared Sn 0 particles in comparison with the citrate or hydrobenzamide stabilized particles for a similar synthesis condition (160, and 90 and 50 nm respectively) [21] .…”
Section: Resultsmentioning
confidence: 99%
“…The strong influence on the properties of final nanoparticles has been reported for different reduction agents (e. g. diethylene glycol, [14] Na[BH 4 ], [3a,15] K[BH 4 ], [16] NaH, [17] n‐BuLi [18] or KC 8 [19] ). Equally important is the role of the precursors, [14] complexing agents modifying the reaction route (e. g. 1,10 N,N‐phenantroline [15b,20] ), or surfactants for the stabilization of the colloid [15b,20–21] . The thermal decomposition of organometallic complexes was also tested as an alternative route for Sn 0 nanoparticles preparation e. g. [[Sn(NMe 2 ) 2 ] 2 ] at 140 °C, [22] [Sn(salen)] at 650 °C [4b] or Bu 3 SnPh (tributylphenyltin) at 700 °C.…”
Section: Introductionmentioning
confidence: 99%
“…The increase in size observed in the sample with a ratio of 5:5 is attributed to an increase in agglomeration due to collision between primary Cu particles that are explosively formed during synthesis in the absence of a surfactant. [21][22][23] The yield of Cu particles obtained through synthesis at 90 C for 20 min with different volume ratios of hydrazine hydrate to ammonium hydroxide, as shown in Fig. 5, was calculated by dividing the weight of Cu particles obtained by the weight of Cu in the precursor.…”
Section: Resultsmentioning
confidence: 99%